White Matter Integrity Deficit Associated with Betel Quid Dependence - Yuan, Fulai; Zhu, Xueling; Kong, Lingyu; Shen, Huaizhen; Liao, Weihua; Jiang, Canhua (Frontiers in Psychiatry, 2017)
Betel quid (BQ) is a commonly consumed psychoactive substance which has been regarded as a human carcinogen. Long-term BQ chewing may cause DSM-IV dependence symptoms, which can lead to decreased cognitive functions, such as attention and inhibition control. Although betel quid dependence (BQD) individuals have been reported with altered brain structure and function, there is little evidence showing white matter microstructure alternation in BQD individuals. The present study aimed to investigate altered white matter microstructure in BQD individuals using diffusion tensor imaging. Tract-based spatial statistics was used to analyze the data. Compared with healthy controls, BQD individuals exhibited higher mean diffusivity (MD) in anterior thalamic radiation (ATR). ROI analysis further revealed the ATR in BQD individuals showed less fractional anisotropy (FA) than that in healthy controls. Correlation analysis showed that both the increase of MD and reduction of FA in BQD individuals were associated with severity of BQ dependence. These results suggested that BQD would disrupt the balance between prefrontal cortex and subcortical areas, causing declined inhibition control.